The development of urban mega-projects in China: A case study of Nantong's metro project. (May 2021) - Zhou, Shutian; Zhai, Guofang; Lu, Yuwen; Shi, Yijun
Since there has been a huge amount of transport infrastructure projects being proposed, planned and constructed over the past decades in China, this article aims to reveal the substantial dynamics of China's rapid development of urban mega-projects. It analyzes Nantong's metro project to use it as a case study – how it was being justified, approved and implemented, and what were the key driving forces within the whole process through official justifications and key informant interview materials. The urban metro system is supposedly an approach to achieve urban development objectives, a tool for growth and a way to a better urban life. We find inter-city competition as an underlying driving force that initiates such urban mega-projects with certain weight given to economic indicators in project appraisals within a largely local government-led and public-invested process. Furthermore, domestic economic performance and changing policy interventions also exert significant influence on project approval and long-term project development. Our findings echo some Western literature on mega-projects development and urban competition, while revealing other features and emerging issues relating to project initiation, proposal examination and implementation specific to the Chinese context.